Review of Robotics Activities to Promote Kindergarteners’ Communication, Collaboration, Critical Thinking, and Creativity - Sophia Rapti; Theodosios Sapounidis; Sokratis Tselegkaridis (Information)
Communication, collaboration, critical thinking, and creativity are core 21st century skills. Meanwhile, educational robotics is regarded as a contributor to their promotion. Hence, education tries to embrace them in school curricula. Yet, there is a lack of reviews in the existing literature presenting the robotics activities used to promote children’s communication, collaboration, creativity, and critical thinking from an early age. Consequently, this study employed a thematic literature review aiming to 1. map the research field of robotics activities suitable for promoting kindergarteners’ skills, 2. facilitate researchers and teachers in their current and future work related to robotics, and 3. provide guidelines and a model flow related to robotics activities for supporting educators in integrating them into their school reality. The PRISMA Flow Diagram and the Atlas.ti software were used to investigate the Scopus database and the Taylor and Francis register. Finally, 16 papers were examined out of 349 initially retrieved and published from 2014 to 2025. Based on our findings, a few interventions have been aimed at fostering kindergarteners’ communication, collaboration, creativity, and critical thinking via educational robotics, but there is rarely a clear record of robotics activities achieving that. Moreover, there is no specific model or guideline for developing such activities in kindergarten.